Case Report: Durable Response to the Combination of Brigatinib and Cetuximab Plus Icotinib in a NSCLC Patient Harboring EGFR L858R-T790M-cis-G796S and L718Q Resistance Mutations Following Progression With Osimertinib - Wang, Yubo; Han, Rui; Zhu, Mengxiao; He, Tingting; He, Yong (Frontiers in Oncology, 2022)
The efficacy of osimertinib is severely limited by the emergence of EGFR C797S, which is detected in either the cis or trans position with T790M when osimertinib is used as a second line treatment, and which is largely identified in combination with an EGFR 19 deletion. The EGFR T790M-cis-G796S mutation, which also occurs in exon 20 as C797S, participates in osimertinib resistance. To date, limited data for overcoming this resistance mutation has been reported. Here, we report data for an advanced NSCLC patient who developed EGFR L858R-T790M-cis-G796S and EGFR L718Q resistance co-mutations following progression with osimertinib. Such a case has rarely been reported and, under chemotherapy guidelines for this situation, no other effective treatment is recommended. The patient in our case experienced remarkable clinical improvement and good tolerance to the combination target therapy of brigatinib and cetuximab plus icotinib. At the time of our patient’s last follow-up and prior to publication, our patient had reached more than nine months of progression free survival (PFS) and felt very well. Our finding provides clinical evidence that the combined target therapy of brigatinib and cetuximab may potentially be an effective treatment strategy for patients with an acquired EGFR T790M-cis-G796S resistance mutation following osimertinib treatment.